The Origin and Advancement of Cardiovascular Physiology in Brazil: The Contribution of Eduardo Krieger to Research Groups - Vasquez, Elisardo C. (Frontiers in Physiology, 2016)
Since 1996, symposia devoted to the discussion of advances in cardiovascular physiology have been alternately organized by Brazilian research groups, most of which were created or joined by PhD trainees of Eduardo M Krieger. Therefore, as Frontiers in Physiology is publishing a topic devoted to the celebration of the 20th edition of the Brazilian Symposium of Cardiovascular Physiology, it is a great opportunity to talk about the contributions of Eduardo Krieger to the development of cardiovascular physiology. In this historical mini-review, first, the influence of the Argentinean group of Bernardo Houssay and Braun Menéndez on cardiovascular physiology in Brazil is discussed. Second, the contribution of Eduardo Krieger to the creation of several of those groups and to the development of science and technology is reviewed. Finally, the origin and consolidation of the group of Vitoria is highlighted as an example of a research group that was influenced by the University of Sao Paulo-Faculty of Medicine of Ribeirao Preto and has trained hundreds of Master and PhD students in the area of cardiovascular research.